'Grapes of Wrath'? Power Spatialities and Aspects of Labour in the Wild Berry Global Commodity Chain. (February 2013) - Hedberg, Charlotta
Despite their central position, workers' relationships have often been a neglected issue in commodity chain approaches. This article analyses how the social relations of workers are affected by economic upgrading in the wild berry global commodity chain (GCC). It is argued that the social effects in a GCC are the result of multiple power spatialities, which must be analysed both according to workers' rights and from a household perspective. In the Swedish wild berry GCC, foreign workers are contracted on a seasonal basis to collect the raw material. The regulated workers, who are principally from Thailand, are subject to social upgrading as well as social downgrading, involving the potential for both exploitation in the Swedish labour market and social empowerment in their homeland. It is concluded that a complex mix of hierarchical, networked and topological power spatialities explain the construction of the wild berry GCC and its effects on worker relations.